Effect of TRIB1 Variant on Lipid Profile and Coronary Artery Disease: A Systematic Review and Meta-Analysis - Baozhu Wei; Yang Liu; Hang Li; Yuanyuan Peng; Zhi Luo (Hindawi-Wiley, 2023)
Background. Emerging evidence indicates tribbles homolog 1 (Trib1) protein may be involved in lipid metabolism regulation and coronary artery disease (CAD) pathogenesis. However, whether TRIB1 gene variants affect lipid levels and CAD remains elusive, this study is aimed at clarifying the effect of TRIB1 variants on lipid profile and CAD. Methods. By searching PubMed and Cochrane databases for studies published before December 18, 2022, a total of 108,831 individuals were included for the analysis. Results. The outcomes of the analysis on all individuals showed that the A allele carriers of rs17321515 and rs2954029 variants had higher low-density lipoprotein cholesterol (LDL-C) and total cholesterol (TC) levels than the noncarriers. Consistently, a higher CAD risk was observed in the A allele carriers. Subgroup analysis indicated that increased LDL-C, TC, and CAD risk were observed in Asian population. Conclusions. Variants of TRIB1 (i.e., rs17321515 and rs2954029) may serve as causal genetic markers for dyslipidemia and CAD in Asian population.